Dirty Dozen Scale: Asaptation to Turkish, Reliability and Validity - Yaşlıoğlu, Duygu Toplu; ATILGAN, ÖZGÜR (Mehmet Akif Ersoy Üniversitesi, 2018)
The aim of this study is to demonstrate the reliability and validity by adapting the scale called "Dark triad dirty dozen" to Turkish Employees who were in managerial positions in any enterprise were selected as research sample. In order to test the reliability and validity of the scale in Turkish language, data collected from two different samples. The results of the exploratory factor analysis and confirmatory factor analysis revealed that three factor structre was confirmed. Since there is no problem in convergent and divergent validity tests, it can be argued that the scale is reliable and valid. In other words, these findings show that the dark triad scale can be used as a reliable and valid tool to be used especially in the field of business management.

Bu çalışmanın amacı, "Dark triad dirty düzine" denilen ölçeği herhangi bir kuruluşta yönetici pozisyonunda bulunan Türk çalışanlarına araştırma örneği olarak seçerek, güvenilirliği ve geçerliliği göstermektir. Ölçeğin Türkçe dilindeki güvenilirliğini ve geçerliliğini test etmek için iki farklı örneklemden veri toplanmıştır. Açıklayıcı faktör analizi ve doğrulayıcı faktör analizi sonuçları, üç faktör yapısının doğrulandığını ortaya koydu. Yakınsak ve farklı geçerlilik testlerinde sorun olmadığı için ölçeğin güvenilir ve geçerli olduğu söylenebilir. Başka bir deyişle, bu bulgular karanlık triad ölçeğinin özellikle işletme yönetimi alanında kullanılmak üzere güvenilir ve geçerli bir araç olarak kullanılabileceğini göstermektedir.
Keywords: Dirty Dozen; Machiavellianism; Psychopathy; Narcissism; Scale Adaptation